Zoning of Mass Movement Occurrence Hazard in West Azarbaijan Province - Hossein Negaresh; Vahid Faizi; Ali Asghar Hodaei; Maryam Mollashahi; Mansooreh Shahhiseini (مخاطرات محیط طبیعی, 2013)
Identification of effective factor on mass movement events and risk zoning is one of the basic tools for mass movement control and appropriate and effective option. Thus, the aim of this study is recognizing effective factors on mass movement and determination hypothetical lands, then pay to mass movement mapping in West Azarbaijan province.  For this reason first of all, important effective factor on mass movement event were determinate. In this study, most mass movement data were obtained base on direct observation. In field study, phenomena location, its approximate measuring, hillside material sampling and region determination was perform. Then, using over laying, accruing different instability zones, field observations and expert opinions deal with to zoning different mass movement in West Azarbaijan province. For this reason Arc GIS and Arc View were used. One of another option in this study is adjusting the phenomena with satellite and aerial picture. The results show that the solifluction and Creeping with about 757898.8 hectare covers almost 20 percent of western Azarbaijan province. Also among the different towns in the province the most probable mass movement is related to Khoy. This mass movement over than 556092.29 hectare approximately includes 14.7 percent of the total mass movements of the western Azarbaijan province.